A Review of Theoretical Perspective on Family Business Governance - Kussudyarsana, Kussudyarsana (Benefit: Jurnal Manajemen dan Bisnis, 2019)
The purpose of this paper is to review governance issue in family firms from several perspectives and discuss about the contribution of transaction cost theory to explain governance mechanism in family firm. In family business literature, the explanation about the governance mechanism movement can be found in Agency theory and Transaction cost Theory. Agency theory supports a foundation for understanding formal control mechanism through hierarchy within firm. Transaction cost economy frequently use to explain governance mechanism for formal control in inter-firm relationship By addressing governance issue in family SMEs, this study contributes to an understanding of connection between characteristic of family SMEs, economic business activities, environmental factors, and governance mechanism.